ISOLATED AND COMBINED IMPACTS OF WEIGHT TRAINING AND LADDER TRAINING ON SELECTED PHYSICAL, PHYSIOLOGICAL AND SKILL PERFORMANCE VARIABLES AMONG WOMEN KABADDI PLAYERS - Selvi, E Santhana; P. Sridar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Background and study aim: To optimize performance in kabaddi, players require a blend of strength, agility, endurance, and speed. While weight training is increasingly popular due to its ability to enhance cardiovascular fitness and functional strength, there is limited understanding of its specific effects on the physical and physiological attributes of kabaddi players. Moreover, skill performance is integral to improving playing abilities. It is important to examine the isolated and combined impact of ladder training and weight training on select physical, physiological, and skill-related performance variables in female kabaddi players. Material and methods: sixty female kabaddi players were randomly assigned to three experimental groups. Experimental group I weight training group (WTG) (N = 15) (Age21.08±0.9, Height: 168.25±3.86, Weight: 65.16±2.32) Experimental group II Ladder training group (N=15) (LTG) (Age: 21.15±1.20, Height: 159.28±2.59, Weight: 60.12±2.42) Experimental group III Combined Training Group (CTG) N = 15) (Age: 21.11±0.52, Height: 168.251±3.86, Weight: 65.16±2.32) and Combined Group (CG) (N = 15) (Age: 21.08±0.9, Height: 160.10±2.11, Weight: 59.17±2.02)their age ranged between 18 and 25. Subjects were randomly selected from the Dr.Sivanthi Aditanar College of Engineering, Tiruchendur, Govindammal Aditanar College for Women, Tiruchendur, Wavoo Wajeeha Women's College of Arts and Science, Kayalpatnam, Thoothukudi, India. Testing Variables: The study assessed various physical, physiological and skill performance variables to evaluate in the impact of combined weight and ladder training. Agility was measured using the Illinois Agility Test, while Leg Explosive Power was assessed through the Standing Broad Jump. Muscular Strength Endurance was determined via the Sit ups test and physiological variables namely VO2 Max was measured by Cooper 12 Minutes run and walk and Breath Holding Time was measured by Nostril Clip Method. Additionally, skill performance variable namely toe touch ability was assessed by Toe Touch Test and considered a dependent variable for overall assessment. Statistical Analysis: statistical analysis using dependent ‘t’ test and Analysis of covariance (ANCOVA) to find out the significance among the mean differences, whenever the ‘F’ ratio for adjusted test was found to be significant, Scheffe’s post-hoc test was used. In all cases level of significance 0.05. Results: Participants who followed the combined weight and ladder training program showed substantial improvements in their physical, physiological, and skill performance indicators when compared to the control group (p < 0.05). Female kabaddi players overall physical, physiological, and skill performance variables were significantly improved by combined weight and ladder training. Conclusion: The combination of weight training and ladder training significantly enhanced the physical, physiological, and skill-related performance of female kabaddi players. This integrated approach proved more effective than either training method alone, demonstrating that a comprehensive training regimen can maximize overall athletic performance and help players achieve their full potential.